Low Expression of Calcitriol Level and Interleukin-10 and Hypoxia-inducible Factor-1 Alpha Expression on Placenta - Suwiyoga, I Ketut; Astawa, I Nyoman Mantik; Jawi, I Made; Putra, I Wayan Artana (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Preeclampsia (PE) is the disease of theories and the second leading cause of maternal and perinatal morbidities and mortalities worldwide. These pathological disturbances will induce inflammation process, oxidative stress, and poor subsequent growth on the fetus including 32% of intrauterine growth restriction, 22% of prematurity, and 24% of neonatal sepsis and asphyxia. There are many theories about the mechanism of PE. In the molecularly level, it is suspected that the low level of calcitriol and interleukin (IL)-10 expressions and high expression of hypoxia- inducible factor (HIF)-1α are the risk factors of PE. AIM: The aim of this study was to prove the low calcitriol level, IL-10, and high expression of HIF-1α in the placenta as the risk factors of PE. METHODS: A nested case–control study was conducted at the Department of Obstetrics-Gynecology Sanglah and Wangaya Hospital Denpasar, Bali, from November 2020 to February 2021. RESULTS: A total of 64 samples of 20–40 weeks gestation age were selected by purposive consecutive sampling, divided into two groups consist of 32 PE as the cases and 32 non-PE as the controls. The material examination, 3 × 3 cm was isolated from the maternal placental surface, was performed at Laboratorium Biomedik Terpadu, Faculty of Medicine, Udayana University. We performed an ELISA technique to find out the calcitriol level; in the other hand, we used immunohistochemistry for detected expression of IL-10 and HIF-1-α. The results revealed the risk of PE in low placental calcitriol levels about 13.8 times higher than in high calcitriol levels (odds ratio [OR] = 13,801, 95% confidence interval [CI] = 4.048–47,050, p = 0.001. The risk of PE in low placental IL-10 expression about 6.6 times higher than in high IL-10 expression (OR = 6600; 95% CI = 2208–19,728; p = 0.001). The risk of PE in high placental HIF-1-α expression about 5.6 times higher than in low placental HIF-1-α expression (OR = 5.622; 95% CI = 1.922–16.450; p = 0.001). CONCLUSION: Low calcitriol level, low IL-10, and high HIF-1-α expression on the placenta were proved as significant risk factors for the development of PE.